2006
DOI: 10.1021/ja066429t
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Control of Enantioselectivity of Amino Acid Recognition by Cholesterol-Armed Cyclen Monolayer at the Air-Water Interface

Abstract: Monolayers of the cholesterol-armed cyclen Na+ complex at the air-water interface display a remarkable, surface pressure dependent enantioselectivity of amino acid recognition. Upon compression of the monolayer, the binding constants of amino acids increase accompanying an inversion of chiral selectivity from the d- to l-form in the case of valine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
106
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 172 publications
(107 citation statements)
references
References 22 publications
0
106
0
1
Order By: Relevance
“…The cross-sectional area of the headgroup of the compound falls approximately in the range of 1. , there was a definite change in the slope of the isotherm, thus suggesting a collapse of the monolayer. [22] Fabrication of monolayers and multilayered films of compound 1 d: Based on the pressure-area isotherm curve, the film depositions were carried out after monolayer compression at two different surface pressures (10 and 40 mN m À1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The cross-sectional area of the headgroup of the compound falls approximately in the range of 1. , there was a definite change in the slope of the isotherm, thus suggesting a collapse of the monolayer. [22] Fabrication of monolayers and multilayered films of compound 1 d: Based on the pressure-area isotherm curve, the film depositions were carried out after monolayer compression at two different surface pressures (10 and 40 mN m À1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The air-water interface has been also used for chiral recognition within membrane components [695][696][697][698][699][700] and/or between amphiphile and aqueous guests [701][702][703][704][705][706][707][708]. Mechanical control of chiral recognition was recently achieved using the novel concept of molecular twisting, as shown in figure 79A, where an octacoordinate sodium complex of a polycholesteryl-substituted cyclen embedded at the air-water interface was used as a molecular host [709]. Helicity of the two possible quadruple helicate structures of this complex is influenced by chirality of the side arms especially when ordered or aggregated at the supramolecular level.…”
Section: Langmuir-blodgett Filmsmentioning
confidence: 99%
“…[20] Recently,w eh ave reported that molecular properties can be tuned by applying amechanical force to amonolayer at the air-water interface. [21][22][23] However,a lthough variation of properties should originate from changes at the molecular level, at that time these could be only inferred.…”
mentioning
confidence: 99%